Determinant Factors of Founding-Family Firms’ Performance in Indonesia - Alex Johanes Simamora (LPPM Universitas Terbuka, 2021)
This research aims to examine the factors that moderate the effect of founding-family firms on performance. Moderating variables include firm reputation, risk-taking behavior, agency costs of managers-shareholders, and agency costs of majority-minority shareholders. Firms' performance includes accounting-based and market-based performance. This research uses 412 manufacturing firm-years listed on the Indonesian Stock Exchange as the research sample. The hypotheses test uses a random-effect regression as the main test and a common-effect regression test as an alternative test. Based on data analysis, firm reputation, risk-taking behavior, agency costs of mangers-shareholders, and agency costs of majority-minority shareholders moderates the effect of the founding family on performance. It indicates that founding-family firms can achieve higher performance if they promote a higher firm reputation, lower risk-taking behavior, and lower agency costs. This research fills the previous findings gap of performance in the founding-family firms. This research captures when founding-family firms can improve performance or experience performance reduction. To the best of the author's knowledge, this research is also the first research that provides a comprehensive picture of determinant factors of founding-family firms' in Indonesia.